Rationality or Social Norms: Overcome Contradiction? - Тевено, Лоран (Journal of Economic Sociology, 2010)
The contraposition of the notions of «social norm» and «rationality» divides sociologists and economists into two confronting camps, which are different in the way of describing the human behavior. These two notions are placed in 1) the established order of social behavior and 2) the equilibrium resulting from rational choice. The author tries to reconsider the initial confrontation in the understanding of rationality and social norms through the analysis of the local relations dynamics and ways of coordination in these relations.